Enhancement of production, income and employment generation through integrated farming system: a case study - Singh, R K; Tripathi, Uttam Kumar (Indian Farming, 2019)
Conventional agriculture is known to cause soil and pasture degradation because it involves intensive tillage, if practised in areas of marginal productivity. An integrated crop-livestock farming system represents a key solution for enhancing livestock production and safeguarding the environment through prudent and efficient resource use. The increasing pressure on land and the growing demand for livestock products makes it more and more important to ensure the effective use of feed resources, including crop residues. An integrated farming system consists of a range of resource-saving practices that aim to achieve acceptable profits and high and sustained production levels, while minimizing the negative effects of intensive farming and preserving the environment. Based on the principle of enhancing natural biological processes above and below the ground, the integrated system is the combination that reduces erosion, increases crop yields, soil biological activity and nutrient recycling, intensifies land use, improving profits can therefore help reduce poverty and malnutrition and strengthen environmental sustainability Integrating crops and livestock serves primarily to minimize risk and not to recycle resources.